You, the complete first season # 1 - Berlanti, Greg; Gamble, Sera; Krieger, Lee Toland, 1983-; Badgley, Penn, 1986-; Lail, Elizabeth; Padovan, Luca; Cherry, Zach; Mitchell, Shay, 1987-; Warner Bros. Home Entertainment (Firm) (Burbank, CA : Warner Bros. Home Entertainment, 2020)
A 21st-century romantic thriller centered around a relationship that gets taken too far, When a brilliant bookstore manager crosses paths with an aspiring writer, his answer becomes clear: anything. As he uses the internet and social media to gather the most intimate of details to get close to her, a charming and awkward crush quickly becomes obsession when he quietly and strategically begins to remove every obstacle, and person, between them.
Disc 1. Pilot -- The last nice guy in New York -- Maybe -- The captain -- Living with the enemy. Disc 2. Amour fou -- Everythingship -- You got me, Babe -- Candace -- Bluebeard's castle.
Based on the book by Caroline Kepnes.
Originally broadcast on television as individual episodes in 2018.
Penn Badgley, Elizabeth Lail, Luca Padovan, Zach Cherry, Shay Mitchell.
Closed-captioned.
Not rated.
DVD, wide screen; Dolby digital 5.1.
Keywords: Stalkers -- Drama; Authors -- Drama; Bookstores -- Employees -- Drama; Social media -- Drama; Man-woman relationships -- Drama; Video recordings for hard of hearing people; Television series; Fiction television programs; Thrillers (Television programs); Video recordings for the hearing impaired; Based on the book